CATEGORY MANAGEMENT IN THE MANAGEMENT OF MINIMUM ASSORTMENT OF THE PHARMACEUTICAL ORGANIZATION - I. F. Samoshchenkova; R. Y. Garankina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
The main principle of the category management is the management of product category as a separate business unit. Category management directs the activities of the pharmaceutical organization to meet the consumer requirements and to provide customers with maximum benefits, which are expressed in the improved assortment,the attractive prices, the reduction of cases of lack of necessary goods, the simplifiedpurchase process. In article the structure of the category management and its role inthe minimum pharmaceutical assortment, a complex of the theoretical and practical issues affecting interrelation of the list of vital and essential medicines and the minimum range of medicines are considered. A number of the new elements supplementing the concept of category management is offered, and the corresponding generalizations are made. The objective of the research is to study the influence of category management on the structure in management of the minimum assortment of medicines of the pharmaceutical organization. Materials and methods. In the course of the solution of the set tasks, the methods of marketing and economic-mathematical analysis were used. Results and discussion. In the analysis of the assortment list of medicines for medical application, which is obligatory for the pharmaceutical enterprises of all forms of ownership, it was revealed that this assortment list is based on the List of Vital Essential and Necessary (VEN) Drugs. The results of the analysis of the obligatory assortment list from the position of internal category management showed that 77.45% are medicines of the list of VEN Drugs; 46.08% are medicines of non-prescription dispensing. Proceeding from this it follows that the worthy, profitable price policy can be conducted only with 22.55% of the list; to develop standards of merchandising with 46.05%. The category management gives an opportunity to the pharmaceutical organization to specify its competitive strategy and to plan actions for management of the range. Conclusion. Advantages of the application of the category management in management of the minimum range of medicines of the pharmaceutical organization consist in the increase in the effectiveness of measures to stimulate demand, competitive pricing, and efficient merchandising. One of the main functions of the category management is to enhance the effectiveness of the interaction between the distributor (the supplier, the manufacturer) and the pharmaceutical organization.